2012
DOI: 10.1063/1.4726212
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced phase transition in potassium azide up to 55 GPa

Abstract: Potassium azide was investigated by Raman scattering spectroscopy up to a pressure of 55.0 GPa by use of diamond anvil cell at room temperature. A pressure-induced reversible phase transition was revealed. The onset of the phase transition was characterized by the hardening of a previously soft lattice mode at 13.6 GPa. This transition is considered a structural phase transition. Compression induces a symmetry reduction, which is indicated by the splitting of the librational modes, the development of infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…The most stable structure is a tetragonal phase with I 4/ mcm symmetry from ambient pressure up to 22 GPa, which is then replaced by a lower-enthalpy C 2/ m structure. Actually, at 13.6 GPa, Raman spectra10 have identified a phase transition that completes at 32.2 GPa, which is in agreement with the C 2/ m phase being stable above 22 GPa. The I 4/ mcm - C 2/ m sequence has also been observed in CsN 3 11.…”
Section: Resultssupporting
confidence: 73%
“…The most stable structure is a tetragonal phase with I 4/ mcm symmetry from ambient pressure up to 22 GPa, which is then replaced by a lower-enthalpy C 2/ m structure. Actually, at 13.6 GPa, Raman spectra10 have identified a phase transition that completes at 32.2 GPa, which is in agreement with the C 2/ m phase being stable above 22 GPa. The I 4/ mcm - C 2/ m sequence has also been observed in CsN 3 11.…”
Section: Resultssupporting
confidence: 73%
“…5,6 Previous studies indicated that inorganic azides undergo a variety of phase transitions, accompanied by the lattice distortion and reorientation of linear azide anions (N 3 À ) during the temperature or pressure induced phase transitions. [7][8][9][10][11][12][13] High-pressure study on inorganic azides has become an interest topic due to the polymerization of azide anions (N 3 À ) can form a high energy density material under high pressure. Polymerization of nitrogen net is pioneered by studies of nitrogen, a phenomenon which was first predicted in 1985 14 and recently achieved.…”
mentioning
confidence: 99%
“…To lower the stabilization pressure, considerable attention has been focused on compressing nitrogen-containing compounds with other elements, including the alkali-metal azides, AN 3 (A = Li, Na, K, Cs), [9][10][11][12] the CNO system (CO/N 2 mixture), 13 the CN system (C 3 N 12 ), 14 etc. Particularly, by using the mixture of NaN 3 and N 2 as the precursor, it has been observed experimentally that the cg-N can be formed at the lower pressure (50 GPa) than that in the pure N 2 .…”
Section: Introductionmentioning
confidence: 99%